(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article explores the foundations of moral education in the works of Sayyid Burhanuddin Termizi, a prominent scholar and spiritual thinker of the Islamic world. His teachings emphasize the purification of the soul, ethical conduct, self-discipline, and the cultivation of virtuous qualities as essential components of personal and social development. The study highlights the relevance of Sayyid Burhanuddin Muhaqqiq Termizi’s ideas for contemporary moral education, showing how his concepts of spiritual refinement, sincerity, and responsibility can contribute to shaping an individual’s character and strengthening the moral fabric of society.